PENGARUH SHOPPING LIFESTYLE, FASHION INVOLVEMENT DAN POSITIVE EMOTION TERHADAP IMPULSE BUYING BEHAVIOR - I Gusti Ayu Imbayani; Ni Nyoman Ari Novarini (Jurnal Ilmiah Manajemen & Bisnis, 2018)
Consumers in making purchases are not often done unplanned and in general consumers prefer a place to shop modern compared with traditional shopping places. Currently the type of modern shopping spot that is popular in the midst of society is the lifestyle shopping center. Increased lifestyle shopping center in Badung regency from year to year make business opportunities for business people, especially in the field of fashion. Shopping lifestyle reflects a person's choice of spending time and money, with the availability of time consumers will have plenty of time to shop and with consumer money will have a high purchasing power               Fashion involvement refers to one's involvement in a fashion product that is driven by the need and interest in the productImpulse buying experienced by consumers can be influenced by positive emotion. This research was conducted to find out the influence of shopping lifestyle, fashion involvement and positive emotion toward impulse buying behavior. Samples taken as much as 220 respondents with the method of purposive sampling                The analysis technique used in this research is Multiple Linear Regression AnalysisThe results with multiple linear regression analysis showed that shopping lifestyle, fashion involvement and positive emotion had a significant positive effect on the impulse buying behavior Keywords :      Shopping Lifestyle, Fashion Involvement, Positive Emotion dan Impulse Buying